Cytosolic cleaved PINK1 represses Parkin translocation to mitochondria and mitophagy. (18th December 2013) - Fedorowicz, Maja A.; de, Rosa L. A.; Rüb, Cornelia; Becker, Dorothea; Huang, Yong; Zhou, Chun; Alessi Wolken, Dana M.; Voos, Wolfgang; Liu, Yuhui; Przedborski, Serge
Abstract PINK1 is a mitochondrial kinase proposed to have a role in the pathogenesis of Parkinson's disease through the regulation of mitophagy. Here, we show that the PINK1 main cleavage product, PINK152, after being generated inside mitochondria, can exit these organelles and localize to the cytosol, where it is not only destined for degradation by the proteasome but binds to Parkin. The interaction of cytosolic PINK1 with Parkin represses Parkin translocation to the mitochondria and subsequent mitophagy. Our work therefore highlights the existence of two cellular pools of PINK1 that have different effects on Parkin translocation and mitophagy.